2017
DOI: 10.1523/jneurosci.3298-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Temporal Expression Profiling in Caenorhabditis elegans Identifies a Core Gene Set Related to Long-Term Memory

Abstract: The identification of genes related to encoding, storage, and retrieval of memories is a major interest in neuroscience. In the current study, we analyzed the temporal gene expression changes in a neuronal mRNA pool during an olfactory long-term associative memory (LTAM) in Caenorhabditis elegans hermaphrodites. Here, we identified a core set of 712 (538 upregulated and 174 downregulated) genes that follows three distinct temporal peaks demonstrating multiple gene regulation waves in LTAM. Compared with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…The conserved site of phosphorylation in the transactivation/KID domain of nematode CREB/CRH-1 has been determined to be Ser29, and previous studies showed that an S29A mutant construct was unable to give rise to CaMKIV/CMK-1 or CaMKK/CKK-1-induced transcription by CRH-1. The use of the S133/S29 phosphorylation site in nematode CRH-1 has been confirmed by several additional studies (Kauffman et al 2010;Chen et al 2016;Freytag et al 2017). In contrast, the sequence of other CREB regulatory phosphorylation sites used in mammals (Mayr and Montminy 2001;Deisseroth and Tsien 2002;Lonze and Ginty 2002;West et al 2002;Altarejos and Montminy 2011) is not conserved in nematode CRH-1 (not shown; we do not exclude the possibility that non-typical phosphorylation sites in CRH-1 might be recognized in the future, but these have not been demonstrated so far).…”
Section: Creb/crh-1 Activity In Nematode Excitotoxicity Is Cell Autonmentioning
confidence: 64%
See 1 more Smart Citation
“…The conserved site of phosphorylation in the transactivation/KID domain of nematode CREB/CRH-1 has been determined to be Ser29, and previous studies showed that an S29A mutant construct was unable to give rise to CaMKIV/CMK-1 or CaMKK/CKK-1-induced transcription by CRH-1. The use of the S133/S29 phosphorylation site in nematode CRH-1 has been confirmed by several additional studies (Kauffman et al 2010;Chen et al 2016;Freytag et al 2017). In contrast, the sequence of other CREB regulatory phosphorylation sites used in mammals (Mayr and Montminy 2001;Deisseroth and Tsien 2002;Lonze and Ginty 2002;West et al 2002;Altarejos and Montminy 2011) is not conserved in nematode CRH-1 (not shown; we do not exclude the possibility that non-typical phosphorylation sites in CRH-1 might be recognized in the future, but these have not been demonstrated so far).…”
Section: Creb/crh-1 Activity In Nematode Excitotoxicity Is Cell Autonmentioning
confidence: 64%
“…GluRs mediate both basic signaling and synaptic plasticity (Rose et al 2003(Rose et al , 2005Rose and Rankin 2006;Emtage et al 2009;Stetak et al 2009). CREB (worm homolog name: CRH-1) and the components of its canonical activation cascade are also well conserved in the worm, and regulate learning and memory and synaptic plasticity Bates et al 2006;Suo et al 2006;Kauffman et al 2010;Nishida et al 2011;Timbers and Rankin 2011;Yu et al 2014;Lakhina et al 2015;Chen et al 2016;Moss et al 2016;Freytag et al 2017;Nishijima and Maruyama 2017;Arey et al 2018;Kaletsky et al 2018). CREB/CRH-1 can be activated by phosphorylation (on a site homologous to Ser133) by the nematode's combined CaMK I/IV homolog CMK-1, whose basal activity is greatly stimulated by CaMKK/CKK-1 Yu et al 2014) (while the other CREB phosphorylation sites seen in mammals do not seem to be conserved in the nematode).…”
mentioning
confidence: 99%
“…Indeed, some of these neurons had been shown to participate in either memory formation (AIB & RIM) or memory retrieval (AIY & RIA (Jin, Pokala and Bargmann, 2016) ). In addition, while we exclusively focused on neurons whose activity was modulated upon memory retrieval, these and other neurons may contribute to memory formation via transcriptional changes (Lakhina et al , 2015;Freytag et al , 2017) . Together, interneurons might act as secondary memory cells that integrate and store information from the upstream primary sensory neurons.…”
Section: Discussionmentioning
confidence: 99%
“…; Freytag et al . ). In contrast, the sequence of other CREB regulatory phosphorylation sites used in mammals (Mayr and Montminy ; Deisseroth and Tsien ; Lonze and Ginty ; West et al .…”
Section: Resultsmentioning
confidence: 97%